Legal Review of Online Gambling Crimes in Indonesia and its Impact on the Younger Generation - Putu Adinda Novianita Martha (International Journal Labs, 2025)
This research examines the growing issue of online gambling crimes in Indonesia and their disproportionate impact on the younger generation. The research problem centers on how technological advancements, coupled with weak law enforcement and socio-economic factors, have facilitated the spread of online gambling, particularly among minors. The objectives of this study are threefold: (1) to analyze the legal framework governing online gambling, (2) to identify the key factors driving youth participation, and (3) to evaluate the effectiveness of existing preventive measures. Using a normative legal research method, this study relies on primary legal sources, such as the ITE Law and Criminal Code, as well as secondary sources, including academic journals and government reports. A conceptual and legislative approach is employed to assess regulatory gaps and societal influences. The findings reveal that while Indonesia has established legal provisions to combat online gambling, enforcement remains inconsistent, and penalties lack deterrent power. Economic pressures, low legal awareness, and easy access to technology exacerbate the problem, leading to severe consequences such as financial loss, mental health issues, and secondary crimes. The study concludes with recommendations for strengthening law enforcement, enhancing digital literacy programs, and fostering multi-stakeholder collaboration to mitigate this crisis. These implications are critical for policymakers, educators, and families aiming to protect vulnerable youth from the dangers of online gambling.